Effect of electron beam irradiation on mechanical properties of unsaturated polyester/nanoclay composites reinforced with carbon and glass fibers. (January 2020) - Razavi, Seyed Mohammad; Ahmadi, Seyed Javad; Rahmani Cherati, Peyman; Hadi, Mina; Ahmadi, Seyed Amir Reza
Highlights: Mechanical properties of UP/nanoclay and UP/nanoclay/fiber composites are studied. Effect of EB irradiation on mechanical properties of composites is investigated. Effect of irradiation on composites is studied using FTIR spectroscopy. Nanoclay enhanced both mechanical and radiation resistance properties of polymer. The composites had desirable properties for applications with radiation exposure. Abstract: Following our previous work on morphology, corrosion resistance and thermal properties of unsaturated polyester (UP)/nanoclay composites, the effect of electron beam (EB) irradiation on mechanical properties of UP/nanoclay composites with various nanoclay contents is investigated in this work. Moreover, influence of EB irradiation with doses of 100, 500 and 1000 kGy on tensile properties and hardness of nanocomposite was examined. FTIR spectroscopy was employed to examine the effect of irradiation on chemical structure of polymer. EB irradiation up to 500 kGy led to the improvement of tensile strength and hardness of the samples. The best mechanical properties were observed for the nanocomposite with 1 wt.% nanoclay content. As the selected nanocomposite, UP/nanoclay(1 wt.%) composite was reinforced by carbon and glass fibers and the effect of EB irradiation on the mechanical properties of the prepared UP/nanoclay/fiber composites was studied. When compared to the fiber-reinforced UP without nanoclay, presence of nanoclay particles in UP/nanoclay/fiber composites resulted in the better mechanical properties and higher radiation resistance. Hence, the UP/nanoclay/fiber composite with proper amount of nanoclay has been shown to be a dependable choice for structural applications in which the material is exposed to ionizing radiations.